Comparative Examination of the Olive Mill Wastewater Biodegradation Process by Various Wood-Rot Macrofungi. (2nd June 2014) - Koutrotsios, Georgios; Zervakis, Georgios I.
Abstract : Olive mill wastewater (OMW) constitutes a major cause of environmental pollution in olive-oil producing regions. Sixty wood-rot macrofungi assigned in 43 species were evaluated for their efficacy to colonize solidified OMW media at initially established optimal growth temperatures. Subsequently eight strains of the following species were qualified: Abortiporus biennis, Ganoderma carnosum, Hapalopilus croceus, Hericium erinaceus, Irpex lacteus, Phanerochaete chrysosporium, Pleurotus djamor, and P. pulmonarius . Fungal growth in OMW (25%v/v in water) resulted in marked reduction of total phenolic content, which was significantly correlated with the effluent's decolorization. A. biennis was the best performing strain (it decreased phenolics by 92% and color by 64%) followed by P. djamor and I. lacteus . Increase of plant seeds germination was less pronounced evidencing that phenolics are only partly responsible for OMW's phytotoxicity. Laccase production was highly correlated with all three biodegradation parameters for H. croceus, Ph. chrysosporium, and Pleurotus spp., and so were manganese-independent and manganese dependent peroxidases for A. biennis and I. lacteus . Monitoring of enzymes with respect to biomass production indicated that Pleurotus spp., H. croceus, and Ph. chrysosporium shared common patterns for all three activities. Moreover, generation of enzymes at the early biodegradation stages enhanced the efficiency of OMW treatment.